Pakeliran Sampakan “Sang Panggung” - Sindhunata Gesit Widiharto; Trisno Santoso (Institut Seni Indonesia Surakarta, 2021)
The combination of puppetry and theater creates an alternative offering a new style of treatment in the form of contemporary theater called “Pakeliran Sampakan”. Pakeliran sampakan carries the mission of modernizing traditional art with the hope of being able to answer the public's saturation regarding spectacle that smells Indonesian culture, especially wayang kulit with the target market the young people. “Sang Panggung” is an adaptation of a story from “Nyi Panggung” written by Eko Tunas which tells about the life behind the scenes of the group of tobong Ketoprak Eka Mardhika. The results of the work represent the form of performances by the tobong ketoprak artists, with the story